Resveratrol Sensitizes Selectively Thyroid Cancer Cell to 131-Iodine Toxicity - Seyed Jalal Hosseinimehr; Seyed Amir Hossein Hosseini (Journal of Toxicology)
Background. In this study, the radiosensitizing effect of resveratrol as a natural product was investigated on cell toxicity induced by 131I in thyroid cancer cell. Methods. Human thyroid cancer cell and human nonmalignant fibroblast cell (HFFF2) were treated with 131I and/or resveratrol at different concentrations for 48 h. The cell proliferation was measured by determination of the percent of the survival cells using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Results. Findings of this study show that resveratrol enhanced the cell death induced by 131I on thyroid cancer cell. Also, resveratrol exhibited a protective effect on normal cells against 131I toxicity. Conclusion. This result indicates a promising effect of resveratrol on improvement of cellular toxicity during iodine therapy.